First report of nocardiosis due to Nocardia asteroides in a domestic canary (Serinus canaria domestica) in Mexico - López-Crespo, Rubén Arturo; Torres-Cervantes, Samantha Miroslava; Pico-Rodríguez, Jwerlly Tatiana; Moreno-Borjas, Manuel Arturo; Martínez-Chavarría, Luary Carolina (Brazilian Journal of Veterinary Pathology, 2023)
Nocardiosis is a multi-systemic disease that has been reported in several species of birds. It is characterized by the development of granulomatous inflammation in several organs, mainly affecting the respiratory system. An adult male domestic canary (Serinus canaria domestica) weighing 14.5 g was received for examination. Multiple nodules were identified in the epicardium, air sacs, and lungs. Histologically these nodules corresponded to granulomas, in which numerous thin, filamentous branching bacteria were identified. Gram stains of the epicardium, air sacs, and lungs revealed many filamentous branching Gram-positive bacteria. These bacteria were also strongly acid-fast positive by Fite-Faraco stain. PCR end-point analysis and sequencing using total DNA extracted from formalin-fixed paraffin-embedded samples of lungs, heart, and air sacs confirmed the presence of Nocardia asteroides. To the best of the authors’ knowledge, this is the first case report of nocardiosis associated with Nocardia asteroides in a Domestic Canary (Serinus canaria domestica) in Mexico.